2004
DOI: 10.1038/sj.jea.7500328
|View full text |Cite
|
Sign up to set email alerts
|

Personal exposure to particulate matter less than 2.5 μm in Mexico City: a pilot study

Abstract: This study was aimed to describe the personal exposure of permanent residents in Mexico City's Metropolitan Area (MCMA) to particulate matter of less than 2.5 mm diameter (PM 2.5 ) during their daily activities. A total of 40 healthy volunteers (30 women and 10 men) with sedentary activities were included. All of them carried a PM 2.5 personal monitor during 13 h and registered their activities in a written diary that classified them in indoor and outdoor microenvironments in each 30 min period. All sample col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 19 publications
0
7
1
Order By: Relevance
“…The median exposure levels reported here for public buses and CC are lower than those reported in the MCMA by Vallejo et al [12] of 101.7 and 62.4 µg m −3 , respectively. However, the average exposure levels reported here are within the range of those reported by Okokon et al [9] (14 ± 5 to 85 ± 39 µg m −3 ) in three European cities for bicycle, public bus and car with open and closed windows.…”
Section: Personal Exposure To Pm 25 In the Mcmacontrasting
confidence: 51%
See 1 more Smart Citation
“…The median exposure levels reported here for public buses and CC are lower than those reported in the MCMA by Vallejo et al [12] of 101.7 and 62.4 µg m −3 , respectively. However, the average exposure levels reported here are within the range of those reported by Okokon et al [9] (14 ± 5 to 85 ± 39 µg m −3 ) in three European cities for bicycle, public bus and car with open and closed windows.…”
Section: Personal Exposure To Pm 25 In the Mcmacontrasting
confidence: 51%
“…In the MCMA, studies have addressed personal exposure to carbon monoxide with the highest and lowest levels observed for private and public transport, respectively [10], and to volatile organic compounds with exposure levels to vehicular related compounds being a factor of 2 greater than observed indoors [11]. Vallejo et al [12] addressed personal exposure to PM 2.5 during transportation within the MCMA by underground, public bus and private car, reporting median exposure levels of 106.2, 101.7 and 62.4 µg m −3 , respectively; however, their study design did not allow for comparison between micro-environment concentrations. This highlights the importance of assessing personal exposure to PM 2.5 during daily commutes using comparable information of modes of transport and routes.…”
Section: Introductionmentioning
confidence: 99%
“…No data about daily temperature or other pollutants concentrations were used because they were not always available from net monitors. Details of personal exposure data were published elsewhere (Vallejo et al, 2004).…”
Section: Pm Measurementmentioning
confidence: 99%
“…One such example is the TEACH (Toxic Exposure Assessment, Columbia/Harvard) study, which measured particle composition in a subway station and in a subway car and observed that the highest exposures occurred in the station (Chillrud et al, 2004). Vallejo et al (2004) placed personal samplers for particulate matter with 50% having aerodynamic mass diameter less than 2.5 µm (PM2.5) on 40 volunteers who recorded their daily activities in 30 minute intervals over a 4-month period. This study demonstrated PM2.5 exposure to be highest during the period when participants rode the subway, although the sampling interval was too large to distinguish times waiting on the platform from times riding in the subway cars.…”
Section: Exposure Assessment In Subway Stationsmentioning
confidence: 99%